Psychopharmacology of autism - McDougle, Christopher J. (Henry Stewart Talks, 2011)
Identification of target symptoms, Pharmacotherapy of motor hyperactivity and inattention, Pharmacotherapy of Interfering repetitive behavior, Pharmacotherapy of Irritability (aggression, self-injury, severe tantrums), Pharmacotherapy of impaired social relatedness, Future directions for research